Lead and cadmium poisoning among workers in small establishments for repairing batteries in Salvador, Brazil - Carvalho, Fernando Martins; Silvany-Neto, Annibal Muniz; Lima, Maria Engrácia Chaves; Tavares, Tania Mascarenhas; Alt, Friedrich (Revista de Saúde Pública, 1985)
A cross-sectional study on lead and cadmium poisoning among workers from the sector engaged in repairing batteries for motor vehicles was carried out. Thirty-nine workers from 19 small establishments, existent in the urban area of Salvador City, State of Bahia, Brazil, were studied. Conditions of hygiene at work place, biological characterization of the workforce and workers' perception of occupational hazards were evaluated and related to blood levels of cadmium, lead, erythroprotoporphyrin and hematocrit. Concentrations of cadmium and lead in blood were determined by flameless atomic absorption spectrophotometry techniques. Thirty-six (92.3%) out of the 39 workers mentioned that their job could be hazardous to their health. Brazilian legislation on safety, hygiene and occupational medicine considers lead and cadmium poisoning as being professional diseases when occurring among people working on repairing batteries. However, only 7 (17.9%) out the 39 workers knew that they were potentially eligible for benefits from present legislation. None of the 39 workers knew that they had been exposed to cadmium nor about the occupational risks arising from this exposure. Geometric mean and standard deviation of cadmium in blood levels was extremely high (0.074; 2.3 &#181mol/1), with 97.4% of the working population exceeding the reference limit of 0.009 &#181mol/1. Mean level of lead in blood was 2.06; 1.4 &#181mol/l. Only one worker presented blood lead level higher than 3.36 mmol/1, which placed him at a higher risk of presenting clinical lead poisoning. Mean level of erythroprotoporphyrin was 0.86; 3.1 &#181mol/l. Two workers had low hematocrit levels : 37 and 38%, respectively. In the whole group, hematocrit levels were poorly correlated with lead or with cadmium levels in blood. A brief, oriented clinical examination did not reveal any clear cases of lead or cadmium poisoning. Higher levels of cadmium and lead in blood were associated with workers' ages above 19 years of age, with amount of time spent in the activity of repairing batteries, poorly ventilated work place, working in establishments which were not incorporated by big bus enterprises and the lack of knowledge about preventive measures against lead poisoning.